New approach to establish a surgical planning in infantile vallecular cyst synchronous with laryngomalacia based on aerodynamic analysis. (March 2023) - Liu, Jinlong; Shao, Yuancheng; Li, Junyang; Zhu, Limin; Gong, Xiaolei; Xue, Lianyan; Shen, Juanya; Li, Youjin
Highlights: Aerodynamics in different epiglottis states were estimated by virtual surgery. Changes in the epiglottis angle have an important effect on the flow field. Aerodynamic analysis may help to predict the airway surgical outcomes. Abstract: Background and objectives: A large proportion of infants with vallecular cyst (VC) have coexisting laryngomalacia (LM). Feeding difficulties, regurgitation, occasional cough, and sleep-disordered breathing are the common symptoms in moderate to severe cases. The surgical management of these cases is more challenging and remains controversial. The purpose of this study is to help surgeons select the effective surgical strategies by computer-aided design (CAD) and computational fluid dynamics (CFD) simulations of the upper airway flow characteristics. Methods: The three dimensional (3D) geometric model of the upper airway was reconstructed based on two dimensional (2D) medical images of the patient with VC accompanied with LM. Virtual surgeries were carried out preoperatively to simulate three possible post-operative states in silico. The different outcomes of virtual surgical strategies were predicted based on computational evaluations of airway fluid dynamics including pressure, resistance, velocity, and wall shear stress (WSS). Results: The CFD results of this study suggested the importance of the angle between the rim of epiglottis and arytenoid epiglottic (AE) fold. There was a small impact on the upper airway flow field while the VC was removed and the angle of epiglottis was unchanged. The partial lifting of epiglottis can further improve the flow field. With performing supraglottoplasty (SGP) and the marsupialization of VC, epiglottis was completely recovered, and the flow field was significantly improved. The clinical symptoms of this patient improved greatly after surgeries and no recurrence or growth retardation were noted during 1-year follow-up. The clinical prognosis was consistent with the prediction of the CFD results. Conclusions: The state of epiglottis needs to be carefully checked to evaluate the necessity of performing further SGP in the patients with VC accompanied with LM. CFD and CAD could be developed as a new approach to help surgeons predict the post-operative outcomes through quantification of the airflow dynamics, and make the optimal and individualized surgical approaches for patients with airway obstruction.